Cleaning process for coated part
By using cerium ammonium nitrate solution on the coated parts for wet dechromium treatment, combined with sandblasting, acidic sandblasting agent soaking, repeated high-pressure spraying and ultrasonic rinsing, the problem of incomplete removal of the surface film layer of the coated parts in the prior art is solved, uniform cleaning and roughening of the surface of the part is achieved, and the quality and efficiency of the coating process are improved.
Patent Information
- Application Number
- CN202411599796.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
AI Technical Summary
The cleaning process of existing coating components is difficult to effectively remove the film layer on the surface of the component, especially in complex structures and edges, resulting in poor cleaning results and affecting product quality.
The wet dechromium treatment was carried out using cerium ammonium nitrate solution, combined with sandblasting, soaking of acidic sandblasting agent, repeated high-pressure spraying and ultrasonic rinsing, and thoroughly clear the film layer on the surface of the coated parts and roughen the surface.
The film layer removal and surface roughening of the surface of the coated component are achieved, ensuring the uniformity and cleanliness of the surface of the component, and improving the quality and efficiency of the coating process.
Smart Images

Figure CN119530748A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material surface coating, and in particular to a purification process of coating parts. Background Art
[0002] In the semiconductor, optical coating, display and other industries, coating generally uses reactive magnetron sputtering or chemical vapor deposition to form a coating on the surface of the substrate. The entire coating process is completed in a chamber. In order to make the coating on the substrate surface more complete, the plate rack holding the substrate and the anti-fog plate in the chamber are usually coated together with the substrate. As the number of coatings increases, the thickness of the film deposited on the plate rack and the anti-fog plate will also increase. When the thickness of the film reaches a certain level, it is easy to fall off. After falling off, pollutants such as particles will be formed, causing pollution to the chamber. In the subsequent coating work, the particles will be mixed into the coating on the substrate surface, affecting the quality of the product. Therefore, it is necessary to regularly process plate racks, anti-fouling plates and other coated parts. The commonly used treatment method is sand blasting. Under the impact of compressed air, high-hardness white corundum and other sand are sprayed to hit the surface of the coated parts, causing the film layer on the surface of the coated parts to fall off and the surface of the coated parts to be roughened. During subsequent use, since the surface of the substrate has been roughened, the deposited film layer has strong adhesion and is not easy to fall off, maintaining a good overall vacuum environment.
[0003] For the BIM mask substrate that needs to be produced, it is a binary mask substrate. The film layer structure that needs to be deposited on the substrate is a CR film, including a three-layer chromium film structure of a bottom layer of chromium oxide, a middle layer of chromium nitride and a top layer of chromium oxynitride. Therefore, during the sputtering process, the thickness of the chromium film sputtered on the coated parts will also be very thick.
[0004] Therefore, a more effective surface film removal process is required for the coated parts used to produce BIM mask substrates. In the Chinese patent with publication number "CN103952664A", the cleaning process for the coated parts includes the following steps: (1) white corundum + brown corundum mixed dry sandblasting, (2) glass bead dry sandblasting, (3) ultrasonic alkaline solution cleaning, (4) tap water rinsing, (5) ultrasonic alkaline solution cleaning, (6) tap water rinsing, (7) primary ultrasonic deionization rinsing, (8) secondary ultrasonic deionization rinsing, and (9) drying. Most of the deposited film layers can be removed through the above steps. However, there are still many problems in the existing cleaning process of coated parts. For example, when manual sandblasting is used, that is, the sandblasting pressure is controlled manually and the sandblasting outlet of the sandblasting tube is moved manually, the corners of the parts are difficult to clean, and the uneven sandblasting surface is easily caused by the uneven residence time of the nozzle or the size of the sandblasting pressure; when an automatic sandblasting machine is used for spraying, the fixed sandblasting pressure is uniform and the distance between the nozzle and the metal parts is uniform, so the parts can be sandblasted evenly and flatly, but for parts with more complex structures and hidden corners, they cannot be sandblasted cleanly and the cleaning effect is not good. Even if ultrasonic alkaline solution cleaning and ultrasonic deionized rinsing and other process steps are used, the surface of the coated parts can only be better cleaned, rather than removing the film layer and roughening the surface. Summary of the invention
[0005] Based on this, the purpose of the present invention is to provide a cleaning process for coated parts, which can obtain metal parts with uniform roughness, avoid the situation where corners cannot be processed due to concealment, and have an outstanding cleaning effect.
[0006] A cleaning process for a coated component comprises the following steps:
[0007] The plated parts are subjected to wet chromium removal treatment using ammonium cerium nitrate solution;
[0008] Carry out the first spray treatment on the coated parts;
[0009] Perform the first hot air drying treatment on the coated parts;
[0010] Perform surface sandblasting on coated parts;
[0011] Perform a second spray treatment on the coated parts;
[0012] Immerse the coated parts in an acid sandblasting agent;
[0013] The coated parts are sprayed for the third time;
[0014] The coated parts are treated by immersion in nitric acid;
[0015] The coated parts are repeatedly subjected to high pressure spray treatment.
[0016] Furthermore, in the wet dechroming treatment, the mass ratio concentration of the ammonium cerium nitrate solution is 10%-20%, the wet dechroming treatment time is 20-30 minutes, and the plated parts are subjected to a polishing treatment with a frequency of 15-25 times / min.
[0017] Furthermore, in the surface sand blasting treatment, the type of sand is white corundum, the sand blasting pressure is 0.6-0.9 MPa, and the sand particle size is 80-300 mesh.
[0018] Furthermore, in the acid sandblasting agent immersion treatment, the acid sandblasting agent immersion time is, and the coated parts are subjected to a blasting treatment with a frequency of 15-25 times / min. After the coated parts are immersed in the acid sandblasting agent, they wait for 30 seconds to perform other treatment steps.
[0019] Furthermore, the sand blasting agent includes a complexing agent, an accelerator and a fog suppressant, and is acidic in nature.
[0020] Furthermore, in the nitric acid soaking treatment, the concentration of the nitric acid solution is 20%-40%, the soaking time is 2-3 minutes, and the coated parts are subjected to a polishing treatment at a frequency of 15-25 times / min.
[0021] Furthermore, in the first spraying treatment, the second spraying treatment and the third spraying treatment, pure water is used for spraying treatment, and a pressure of 0.3-0.5 MPa is applied during spraying.
[0022] Furthermore, in the first hot air drying treatment and the second hot air drying treatment, after the coated parts are drained, hot nitrogen is used to blow dry the coated parts.
[0023] Furthermore, in the repeated high-pressure spraying treatment, pure water is used for repeated spraying treatment, and a pressure of 3-5 MPa is applied during the spraying.
[0024] Furthermore, the method further comprises the steps of:
[0025] Ultrasonic rinsing treatment is performed on the coated parts that have been repeatedly treated with high-pressure spraying;
[0026] The coated parts are subjected to a second hot air drying treatment.
[0027] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the purification process flow of the coating components of the present invention.
[0029] Figure 2It is a schematic diagram of the initial image and the final image of the coating component of the present invention within the optimal parameter range during the cleaning process.
[0030] Figure 3 It is a schematic diagram of the initial image and the final image of the coating component of the present invention when some parameters are outside the optimal parameter range during the cleaning process.
[0031] Figure 4 It is a schematic diagram of the final image comparison of partial operation requirements of the coating component of the present invention in the cleaning process being within and outside the optimal range. DETAILED DESCRIPTION
[0032] The applicant learned that this very thick chromium film can theoretically be cleaned by using a chemical wet method of ammonium cerium nitrate solution, but in fact the prior art does not use this method because ammonium cerium nitrate is difficult to be completely cleaned and a small amount of it remains on the surface of the component. Even if the residual amount is very small, it will still evaporate into the cavity during subsequent use, corroding and damaging various components in the cavity, causing a significant negative impact on the quality of the chromium film. To this end, the applicant tried to adjust and add other processing steps to completely remove the residue of ammonium cerium nitrate, which has an outstanding film removal effect while ensuring that it will not affect the normal operation of the coated components.
[0033] See also Figure 1 As shown in Table 1, the cleaning process of the coating component of the present invention comprises the following steps:
[0034] (1) Performing wet chromium removal treatment on the coated parts. Specifically, since the coated parts are made of aluminum and aluminum alloy materials, and the attached substances are chromium, chromium target sputtering compounds and chromium evaporation compounds, the coated parts to be dechromed are placed in a tray, and ammonium cerium nitrate solution is poured onto the surface of the coated parts. During dechroming, the tray and the coated parts are tossed up and down to fully contact with the ammonium cerium nitrate solution, wherein the mass ratio concentration of the ammonium cerium nitrate solution is 10%-20%, the wet chromium removal time is 20-30 minutes, and the tray is tossed at a frequency of 15-25 times / min; preferably, the mass ratio concentration of the ammonium cerium nitrate solution is 15%, the wet chromium removal time is 25 minutes, and the tray is tossed at a frequency of 20 times / min. The ammonium cerium nitrate cleaning process reacts with the attached substances to remove the main body of the film layer of the coated parts, thereby obtaining coated parts without a film layer.
[0035] (2) The plated parts after wet chromium removal are subjected to a first spray treatment. Specifically, pure water is used for spray treatment, and a pressure of 0.3-0.5 MPa is applied during spraying. After wet chromium removal, some ammonium cerium nitrate solution and other salt solutions reacted with the ammonium cerium nitrate solution will remain on the surface of the plated parts. The sprayed pure water will take away the ammonium cerium nitrate solution and other salt solutions remaining on the surface of the plated parts under a certain pressure; preferably, pure water with a pressure of 0.75 MPa is used in the first spray treatment.
[0036] (3) The rinsed coated parts are subjected to the first hot air drying treatment. Specifically, since the liquid to be dried is pure water, it can be directly removed by hot air drying. In order to save drying time and energy consumption, the coated parts are first drained. In order to prevent the drying gas from reacting with the chemical substances used in the subsequent treatment, the coated parts are blown dry with hot nitrogen. The surface of the coated parts can be dried with hot air to prevent the possible residual ammonium cerium nitrate solution from adhering to part of the sand during the subsequent surface sandblasting process, thereby affecting the sandblasting effect. After the residual ammonium cerium nitrate solution is dried, only the ammonium cerium nitrate solute remains, which will be completely removed by the sandblasting process.
[0037] (4) The coated parts that have undergone the first hot air drying treatment are subjected to surface sandblasting. Specifically, under the push of compressed air, high-hardness white corundum and other sand are sprayed to impact the surface of the coated parts to roughen the surface of the coated parts. The entire treatment process only involves physical impact, so the sandblasting pressure and the sand particle size directly determine the effect of the roughness of the sandblasting surface; wherein, the sandblasting pressure is 0.6-0.9MPa, and the sand particle size is 80-300 mesh, to ensure that the sandblasting surface can reach the required roughness but will not be pierced and damaged; preferably, white corundum sand is used, the sandblasting pressure is 0.75MPa, and the sand particle size is 200 mesh.
[0038] (5) The coated parts that have been subjected to surface sandblasting are subjected to a second spraying treatment. Specifically, the spraying treatment is still carried out by applying pure water at a pressure of 0.3-0.5 MPa, and 0.4 MPa is preferably selected to wash away the white corundum and other sands remaining on the surface of the coating; preferably, pure water at a pressure of 0.4 MPa is used in the second spraying treatment.
[0039] (6) The coated parts after the second spraying treatment are soaked in an acidic sandblasting agent. Specifically, the sandblasting agent is a compound of a complexing agent, a accelerator, a fog suppressant and other materials. It has a certain corrosiveness and can react chemically with the oxide layer on the surface of the aluminum alloy, dissolve it and convert it into a substance that can be removed, so that the surface of the coated parts is further roughened and the roughening degree of the surface of the coated parts is uniform. The acidic sandblasting agent is used to add more hydrogen ions to the sandblasting agent, which can make the chemical reaction during the soaking process more intense, accelerate and strengthen the removal effect during the sandblasting process. Among them, the soaking time of the acidic sandblasting agent is 2-5 minutes, and the coated parts need to enter the next step within 30 seconds after being soaked in the acidic sandblasting agent to prevent the coated parts from being damaged by excessive corrosion; preferably, the soaking time of the acidic sandblasting agent is 3 minutes, and the coated parts wait for 15 seconds after being soaked in the acidic sandblasting agent before proceeding to the next step, and the tossing frequency of the tray is 20 times / min.
[0040] (7) The coated parts soaked in the acidic sandblasting agent are subjected to a third spraying treatment. Specifically, the spraying treatment is still carried out using pure water at a pressure of 0.3-0.5 MPa to dissolve and remove most of the residual acidic sandblasting agent; preferably, pure water at a pressure of 0.4 MPa is used in the third spraying treatment.
[0041] (8) The coated parts after the third spray treatment are soaked in nitric acid. Nitric acid is added to the tray to react with the removable substances formed after soaking in the acid sandblasting agent, so as to dissolve the removable substances and facilitate subsequent cleaning; wherein the concentration of the nitric acid solution is 20%-40%, the soaking time is 2-3 minutes, and the frequency of the tray is 15-25 times / min; preferably, the concentration of the nitric acid solution is 30%, the soaking time is 2.5 minutes, and the frequency of the tray is 20 times / min.
[0042] (9) Repeatedly spray the coated parts after nitric acid immersion treatment with high pressure. Specifically, pure water with a pressure of 3-5 MPa is used for repeated spraying to remove the residual nitric acid solution and the substances after the reaction of nitric acid and the removable substances. Preferably, the spraying pressure of pure water is 4 MPa.
[0043] (10) Performing ultrasonic rinsing on the coated parts that have been repeatedly treated with high-pressure spraying. Specifically, the ultrasonic frequency is set between 28-40 kHz, and pure water is used for multiple pure water rinsing such as flushing, overflow, nitrogen bubbling, and circulating overflow to thoroughly remove various possible impurities remaining on the surface of the coated parts.
[0044] (11) The coated parts that have been ultrasonically rinsed are subjected to a second hot air drying treatment. Specifically, since the liquid to be dried is still pure water, it can be directly removed by hot air drying. In order to save drying time and energy consumption, the coated parts are first drained. In order to prevent the drying gas from reacting with the chemical substances used in subsequent treatments, hot nitrogen is used to blow dry the coated parts.
[0045]
[0046] Table 1
[0047] The above steps can completely and evenly remove the film layer of the coated parts, and there is no chemical residue that affects the normal operation of the coated parts. Please refer to Figure 2 , Figure 2 The left picture is the initial image of the coated part. The darker grayscale shows the complete initial chrome film. The right picture is the final image of the coated part after cleaning. The aluminum luster of the coated part itself can be seen. The chrome film is removed evenly and thoroughly, and the surface roughness is obvious, with excellent cleaning effect.
[0048] In order to better verify the cleaning process effect of the coated parts of the present application, multiple experimental tests are repeated, various parameters are continuously changed, recorded in the corresponding table, and necessary images of the coated parts are visually observed or photographed for comparison, based on which the optimal range of each parameter is analyzed and verified.
[0049] Specifically, please refer to Table 2, which shows the project parameter table obtained when the treatment time of adding ammonium cerium nitrate solution is lower than the optimal range, and shows the cleaning effect of the plated parts after each step of process treatment. It can be seen that due to the short wet chromium removal treatment time, there is residual chromium on the surface of the plated parts that has not been removed. Although the parameters of the subsequent steps meet the optimal range given in Table 1, the residual chromium leads to the superposition of problems. The plated parts obtained after each step of process treatment have the problem of incomplete cleaning. Please refer to Figure 3 , Figure 3 The top middle image shows the initial image of the coated part. You can see that the darker grayscale represents a thicker chrome film. Figure 3 The lower middle part shows the final image of the coated parts after cleaning. It can be seen that most of the chrome film on the coated parts has been removed after the cleaning process. However, the residual chromium during the wet chromium removal treatment affects the reaction rate of the acid blasting agent, which in turn affects the uniformity of the reaction, resulting in different color areas in the right third of the final image, which are darker gray than other areas.
[0050]
[0051] Table 2
[0052] Please refer to Table 3, which shows the cleaning effect of the coated parts after each process step when the parameters are within the optimal range described in Table 1. It should be noted that Table 1 requires entering the next process step within 30 seconds after the acid sandblasting agent immersion treatment. In Table 3, this range requirement is met, and the next process step is entered 20 seconds after the acid sandblasting agent immersion treatment. Therefore, the images of the coated parts obtained after each process treatment are presented normally.
[0053]
[0054] Table 3
[0055] Please refer to Table 4. The parameters in Table 4 are exactly the same as those in Table 3, but the difference is that in Table 4, the next process step is entered 40s after the acid sandblasting agent soaking treatment. Since the sandblasting agent will drip and evaporate on the sample during the waiting period, the upper part will react less, while the lower part will react more, forming an uneven reaction. In addition, the overall time extension causes the overall reaction. Therefore, the color of the sample appears darker after the acid sandblasting agent soaking treatment. Please refer to Figure 4 The left picture shows the final image after 20s of acid sandblasting agent immersion and entering the next process step, and the right picture shows the final image after 40s of acid sandblasting agent immersion and entering the next process step. It can be clearly seen that although both images are very uniform, the color of the right picture is darker, which is caused by the long waiting time after the acid sandblasting agent immersion treatment.
[0056]
[0057] Table 4
[0058] After the cleaning process of the coated parts is completed, the coated parts are inspected. Specifically, manual visual inspection is used to mainly check whether the surface roughness of the coated parts is uniform and whether there are watermarks.
[0059] The process steps of the present invention are designed to first perform sandblasting and then perform sandblasting agent treatment, that is, the rough surface formed on the surface of the coated component after sandblasting is sandblasted, so that the sharp-angle film layer on the surface of the rough surface is processed after sandblasting, and the surface is sanded evenly; and by accurately controlling the process parameters, concentration and treatment time of each step, the surface of the coated component will not be excessively corroded or damaged, thereby affecting its performance and aesthetics; and wet chromium removal is adopted before sandblasting, so that the film layer of the coated component is completely and evenly removed.
[0060] The above-mentioned embodiment only expresses one implementation mode of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A cleaning process for a coated component, characterized in that: Includes steps: The plated parts are subjected to wet chromium removal treatment using ammonium cerium nitrate solution; Carry out the first spray treatment on the coated parts; Perform the first hot air drying treatment on the coated parts; Perform surface sandblasting on coated parts; Perform a second spray treatment on the coated parts; Immerse the coated parts in an acid sandblasting agent; The coated parts are sprayed for the third time; The coated parts are treated by immersion in nitric acid; The coated parts are repeatedly subjected to high pressure spray treatment.
2. The cleaning process for coating components according to claim 1, characterized in that: In the wet dechroming treatment, the mass ratio concentration of the ammonium cerium nitrate solution is 10%-20%, the wet dechroming treatment time is 20-30 minutes, and the plated parts are subjected to a polishing treatment with a frequency of 15-25 times / min.
3. The cleaning process for coating components according to claim 2, characterized in that: In the surface sand blasting treatment, the type of sand is white corundum, the sand blasting pressure is 0.6-0.9 MPa, and the sand particle size is 80-300 mesh.
4. The cleaning process for coating components according to claim 3, characterized in that: In the acid sandblasting agent immersion treatment, the acid sandblasting agent immersion time is, and the coated parts are subjected to a blasting treatment with a frequency of 15-25 times / min. After the coated parts are immersed in the acid sandblasting agent, other treatment steps are performed within 30s.
5. The cleaning process for coating components according to claim 4, characterized in that: The sand blasting agent comprises a complexing agent, an accelerator and a fog suppressant, and is acidic in nature.
6. The cleaning process for coating components according to claim 5, characterized in that: In the nitric acid soaking treatment, the concentration of the nitric acid solution is 20%-40%, the soaking time is 2-3 minutes, and the coated parts are subjected to a blasting treatment at a frequency of 15-25 times / min.
7. The cleaning process for coating components according to claim 6, characterized in that: In the first spraying treatment, the second spraying treatment and the third spraying treatment, pure water is used for spraying treatment, and a pressure of 0.3-0.5 MPa is applied during spraying.
8. The cleaning process for coating components according to claim 7, characterized in that: In the first hot air drying treatment and the second hot air drying treatment, after the coated parts are drained, hot nitrogen is used to blow dry the coated parts.
9. The cleaning process for coating components according to claim 8, characterized in that: In the repeated high-pressure spraying treatment, pure water is used for repeated spraying treatment, and a pressure of 3-5 MPa is applied during the spraying.
10. The cleaning process for coating components according to claim 9, characterized in that: Also includes the steps: Ultrasonic rinsing treatment is performed on the coated parts that have been repeatedly treated with high-pressure spraying; The coated parts are subjected to a second hot air drying treatment.
Citation Information
Patent Citations
Surface pretreatment process for diamond-like carbon coated workpiece
CN103952664A